An approach based on mean line assumption for preliminary design of turbochargers' rotors. (26th June 2019) - Bourabia, Lakhdar; Cerdoun, Mahfoudh; Khalfallah, Smail; Chettibi, Taha
Lacks are recorded in the preliminary design of turbocharger's rotors and there is yet no conclusion about the superiority of any approach to provide an initial conception. The present paper is devoted to the preliminary design of turbochargers' rotors which is based on the equations of conservation and the velocity diagram. This preliminary design is performed following two steps. First, a methodology is proposed and implemented to define all the required design geometrical parameters which are, then, used in the second step via the components of the software ANSYS to generate the 3D geometry. The resulting design is after evaluated using streamline performance analysis for the impeller and ANSYS CFX for the rotor. To validate the present approach, rotor and impeller design are carried out in which the inputs parameters were chosen similar to an existing turbocharger. The comparison is made in terms of performances showing a good agreement.